C Arm confirmation of lung isolation in pediatric patients undergoing video-assisted thoracoscopic decortication: A retrospective case series - Vrushali Ponde; Anagha Patil; Tripti Nagdev; Anuya Gursale (Journal of Anaesthesiology Clinical Pharmacology, 2022)
Video-assisted thoracoscopic surgery (VATS) is a frequently performed procedure in children which requires an efficient technique for lung isolation. Unavailability of appropriate size double-lumen tubes (DLT) for children and fiber optic scopes inspired us to create our own technique for lung isolation. This retrospective case series aims to describe our technique of C arm-aided endotracheal tube (ETT) placement for one-lung ventilation in these patients. 15 patients, aged 3 months to 10 years posted for VATS were recruited. Standard monitoring, general anesthesia and Lung isolation done as per the described protocol. Mean, standard deviation, and 95% Confidence interval was used. The mean age and weight was 43.93 months was 16.4 kg respectively. All right bronchus intubations were achieved in the first attempt. Of the 8 left bronchus intubations, 4 needed more than one attempt with a stylet inserted with a gentle J-shaped curve. Mild desaturation, seen in 2 patients during surgery was corrected with neck extension and increasing the FiO2. None of the cases required withdrawal of the tube into the trachea. One-lung anesthesia was achieved successfully in all the cases using C Arm with routine ETT.